OPERATIONS STRATEGY OF AHLI PEST TO SURVIVE IN COMPETITIVE MARKET - WANDI S. P. SIAGIAN (NIM 29316046), ANDRE
The Indonesian services sector has elevated in the last ten years. Urbanization growth and increasing consumer awareness about health and hygiene are factors expected to increase pest control service usage over the forecast period. Ahli Pest is one of the players in the industry is offering pest and termite control focusing on Jabodetabek market. The number of customer complaint and employee overtime rate is relatively high that indicates there are problems in operations division. Those issues effect high operation expenses which are not accordance with companyÃ‚Â’s revenue and profit loss. Those problems must be solved as soon as possible so the company can survive. In order to identify the operations issue that is faced by the company, a research is conducted through qualitative research by using interview to collect information from CEO and Operation Manager. The problems that occurs in the company will be analyzed by using Fishbone Diagram supported with root cause analysis in order to find the main problem. As result, there are three main problems that have to be solved immediately. They are high rate of employee overtime, high number of customers complaint, and high operating expenses. Those problems are related one to another. TQM is used to formulate proper operations strategy so it could be used to design policies by the company. In addition, Profit Plan Scenario is used so the company could set monthly sales target to fund operation expenses. Strategy formulation will be conducted based on root cause and the result is alternative solutions. Based on analysis, proper operations strategies are required in order to solve issues which are faced by the company in order to survive and grow in the competitive market. Ahli Pest needs to focus on creating policies, systems, and set sales target in order to survive and grow in the market.